Ixekizumab trough concentrations in psoriasis: Paving the way towards personalised therapy: A cohort study - Lisa Schots; Rani Soenen; Debby Thomas; Annelies Stockman; Erwin Dreesen; Anke Eylenbosch; Jo Lambert (JEADV Clinical Practice)
Abstract Background Biologics for psoriasis demonstrate varying clinical outcome in real‐world practice, implying potential under‐ and overexposure. Objectives In this prospective cohort study we aimed to develop and validate an in‐house sandwich‐type enzyme‐linked immunosorbent assay (ELISA) for ixekizumab (IXE), and to explore whether there is an exposure‐response relationship in standard maintenance dose for IXE, and whether patient factors influence IXE exposure and clinical outcome. Methods This was a prospective, multicentric, cohort study in psoriasis patients treated with IXE according to standard dosing regimen (BIOLOPTIM‐IXE). IXE trough concentrations (TCs) in sera collected at multiple timepoints were measured using an in‐house immunoassay. Results Using MA‐IXE117E12 and MA‐IXE100F5‐biotin as the capture and detection antibodies, respectively, an ELISA was developed with an exposure‐response curve ranging from 10 to 0.16525 ng/mL. One hundred‐fifteen steady‐state serum samples from 48 patients (17 [35.4%] bio‐experienced; median body weight, 81.5 kg) were measured. Optimal responders (Psoriasis Area and Severity Index [PASI] ≤ 2) had significantly higher TCs than suboptimal responders (PASI > 2) (median TCs, 4.4 and 3.0 μg/mL, respectively; p = 0.026). Median cohort IXE TC was 4.1 µg/mL [2.8−6.1]. An optimal steady‐state IXE TC of 3.4 µg/mL was identified for clinical outcome defined by absolute PASI. Median TCs and absolute PASI were significantly lower and worse, respectively, in patients ≥ 90 kg (p < 0.001 and p = 0.013, respectively) and in bio‐experienced subjects (p < 0.001 and p = 0.029, respectively). Conclusions This study identified an IXE exposure‐response relationship and an optimal effective steady‐state TC of 3.4 µg/mL in real‐world psoriasis patients, revealing the potential of therapeutic drug monitoring in optimising IXE use.